The Sustainable Development Goals (SDGs): a rising tide lifts all boats? Global reporting implications in a post SDGs world. Issue 3 (12th February 2021) - Elalfy, Amr; Weber, Olaf; Geobey, Sean
Abstract : Purpose: We investigate the integration of the United Nation's Sustainable Development Goals (SDGs) into the Global Reporting Initiative (GRI)– based reporting thus exploring the factors that influence the adoption of the SDGs by organizations. Design/methodology/approach: We analyzed the GRI dataset provided by the GRI data secretariat. We analyzed 14, 308 reports provided by 9, 397 organizations between 2016 and 2017. Findings: Larger organizations are more likely to integrate the SDGs into their reporting than smaller organizations. Secondly, publicly listed firms are more likely to address the SDGs. Thirdly, industries with higher sustainability impacts are more likely to address the SDGs in their reporting. Fourthly, our data confirm a regional effect with regard to SDG reporting. Moreover, organizations that follow international sustainability guidelines and standards such as becoming a member of the GRI Gold Community or using the GRI Content Index services and having external assurance are more likely to report on the SDGs. Research limitations/implications: Corporations play an essential role in the achievement of the SDGs, which shape the future of the world's sustainable development. Nevertheless, SDGs reporting needs more research to analyze the factors that can influence it. The study contributed to the academic literature on CSR and legitimacy theory by analyzing institutional and regional factors that impact SDGs reporting. Practical implications: The study provides insights about the integration of the SDGs into organizational reporting and accounting, including the adoption of the SDGs by small and medium enterprises (SMEs) and the benefits of the SDGs as a framework for strategic corporate sustainability. Social implications: A global sustainability framework, such as the SDGs can be integrated into organizations sustainability reporting and accounting in a meaningful way. Originality/value: This is the first study that analyzes the integration of the SDGs into GRI-based reporting. The study contributes to legitimacy theory by highlighting the factors, which contribute to the legitimacy-based adoption of the SDGs, including organizational size, being publicly listed, being from high-impact industries and certain global regions, etc. SDG reporting can help firms increase their organizational legitimacy across their stakeholders.